Burden of premature mortality in Malaysia. - Ummi Nadiah Yusoff,; Diana Mahat,; Azahadi Omar,; Teh, Chien Huey; Norzawati Yoep,; Riyanti Saari, (Universiti Kebangsaan Malaysia, 2013)
Mortality estimates are important parameters for health monitoring and are routinely used as evidence for health policy and planning. This study aimed to estimate the mortality component of Burden of Disease in Malaysia in 2008.